Chromosome-level genome assembly and single-cell analysis unveil molecular mechanisms of arm regeneration in the ophiuroid Ophiura sarsii vadicola - Qin-Zeng Xu; Yi-Xuan Li; Wen-Ge Shi; Yue Dong; Zhong Li; Jack Chi-Ho Ip; Matthew P. Galaska; Chen Han; Qian Zhang; Yu-Yao Sun; Lin-Lin Zhao; Kai-Ming Sun; et al. (Genome Biology)
Abstract Background Ophiuroids, belonging to Ophiuroidea in Echinodermata, possess remarkable regenerative capacities in their arms, relying on cellular recruitment and de-differentiation. However, limited high-quality genomic resources have hindered the investigation of the underlying molecular mechanisms of ophiuroid regeneration. Results Here, we report a chromosome-level genome of Ophiura sarsii vadicola, 259.28 Mbp in length with a scaffold N50 length of 66.91 Mbp. We then perform bulk and single-cell RNA sequencing analysis to investigate gene expression and cellular dynamics during arm regeneration. We identify five distinct cellular clusters involved in the arm regeneration and infer the dynamic transformations from sensory stimulation to injury response, wound healing, and tissue regeneration. We find that progenitor cells derived from connective tissue cells differentiate into muscle, cartilage, endothelial, and epithelial cells. Pseudotime analysis indicates that muscle differentiation occurs early in the regeneration process. Conclusions Our genomic resource and single-cell atlas shed light on the mechanisms of organ regeneration in ophiuroids.